Designing User Interface of a Mobile Learning Application by Using a Design Thinking Approach: A Case Study on UNI Couse - Dandi Saputra; Rafiati Kania (Journal of Marketing Innovation (JMI), 2022)
UNI Couse, a mobile learning application product developed by CV Unindo Hestama Kreatif, is a mobile learning application that newly transform its system from web-based e-learning platforms. The incapability of web-based systems to gain a better experience with wider consumers trigger the transformation. Designing a mobile learning application is a strategy to increase the usability of the existing e-learning system in a higher variety of services as well as more users. This study utilizes a design thinking approach to understand what user feels and need in their experience of using a mobile application. This approach consists of five stages and is divided into three processes: understanding, designing, and evaluating. This study illustrates a step-by-step design thinking implementation as well as the result of each stage.  User testing assesses the usability of the mobile learning application. Finally, design thinking implementation reveals that more users feel comfortable with the apps because all features are needed and easy to understand. The design thinking approach has successfully helped UNI Course to create mobile learning applications that satisfy the users.